Glycaemic Changes Among Children and Adolescents With Type 1 Diabetes Mellitus Before and During Ramadan Fasting Using Continuous Glucose Monitoring - Teoh, Sze Teik; Hussain, Suhaimi; Hong, Janet Yeow Hua (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Objectives . This study described and compared glycaemic changes with the use of the following Continuous Glucose Monitoring (CGM) metrics: time in range, time in hyperglycaemia and time in hypoglycaemia from retrospective CGM data among children and adolescents with Type 1 Diabetes Mellitus (T1DM), before and during Ramadan to better understand the impact of fasting during this season. Methodology. This study was conducted in 2 tertiary centres: Hospital Putrajaya (HPJ) and Hospital Universiti Sains Malaysia (HUSM) from February to May 2020. Muslim T1DM patients between ages 8 to18 who intended to fast during Ramadan were given Ramadan-focused education. CGM iPro2® (Medtronic) was used before and during Ramadan, complemented by finger-prick glucose monitoring or self-monitoring of blood glucose (SMBG). Results. Of the 32 patients, only 24 (12 female) were analysed. Mean age was 13.6 ± 3.1 years old, mean HbAlc was 9.6 ± 1.9% and mean duration of illness was 5.4 ± 3.4 years. Majority (91.7%) were on multiple dose injections (MDI) while only 8.3% were on continuous subcutaneous insulin infusion (CSII). All fasted in Ramadan without acute complications. Retrospective CGM analysis revealed similar results in time in range (TIR), time in hyperglycaemia and time in hypoglycaemia before and during Ramadan, indicating no increased hypoglycaemic or hyperglycaemic events related to fasting. Glycaemic variability before Ramadan as measured by the LBGI, HBGI and MAG, were similar to values during Ramadan. Conclusion. Ramadan fasting among T1DM children and adolescents, by itself, is not associated with short-term glycaemic deterioration. T1DM youths can fast safely in Ramadan with the provision of focused education and regular SMBG.